2020
DOI: 10.1093/ajcn/nqz285
|View full text |Cite
|
Sign up to set email alerts
|

Increasing oat β-glucan viscosity in a breakfast meal slows gastric emptying and reduces glycemic and insulinemic responses but has no effect on appetite, food intake, or plasma ghrelin and PYY responses in healthy humans: a randomized, placebo-controlled, crossover trial

Abstract: Background The viscosity of oat β-glucan (OBG) determines its effect on serum cholesterol and glycemic responses, but whether OBG viscosity affects gastric emptying, appetite, and ad libitum food intake is unknown. Objectives We aimed to determine the effect of altering the amount or molecular weight (MW) and, hence, viscosity of OBG in a breakfast meal on the primary endpoint of food intake at a subsequent meal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 48 publications
0
39
0
1
Order By: Relevance
“…Contradictory to these studies, Wolever et al. (2019) reported a delay in the gastric emptying half‐time of breakfast cereals (semisolid) with higher viscosity, which in the study were consumed with bread (solid), and the delay was consistent until 90 min after consumption of the meals. The study also reported that higher viscosity of the semisolid phase of the test meals led to lower glycemic response of the meals.…”
Section: Food Structure Gastric Digestion and Glycemic Response Relationshipmentioning
confidence: 94%
“…Contradictory to these studies, Wolever et al. (2019) reported a delay in the gastric emptying half‐time of breakfast cereals (semisolid) with higher viscosity, which in the study were consumed with bread (solid), and the delay was consistent until 90 min after consumption of the meals. The study also reported that higher viscosity of the semisolid phase of the test meals led to lower glycemic response of the meals.…”
Section: Food Structure Gastric Digestion and Glycemic Response Relationshipmentioning
confidence: 94%
“…This study also demonstrated that viscosity would determine the effect of the β-glucans. It is hypothesized that by forming viscous solutions and retaining water in the digestive tract stool volume is increased and homeostasis of blood glucose levels are improved [ 37 , 94 ].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Second, beta-glucans are considered active ingredients in treatments aimed at improving immunity in a variety of disorders, including cancer [ 52 ]. Various forms of oral formulations are promoted worldwide as over-the-counter remedies, and some formulations are being also considered for either systemic or oral administration and undergoing clinical evaluation [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Third, β-(1,3)- d -glucans may become undesirable contaminants in pharmaceutical products, where they are inadvertently introduced during manufacturing either through certain types of personal protective equipment (PPE) suits and other cellulose-based materials (e.g., cellulose-acetate filters, cotton plugs) used in manufacturing facilities or from fungal contamination of starting materials (e.g., sucrose and sucrose-containing buffers), tools, and equipment [ 32 , 61 ] ( Table 2 ).…”
Section: Overview Of Beta-glucansmentioning
confidence: 99%